Ion-acoustic supersolitons in the presence of non-thermal electrons - Singh, S. V.; Lakhina, G. S. (My University, 2015)
A great deal of interest has been generated in the literature to study the newly found structures known as supersolitons. Theoretical models are being developed to understand these unusual electric field structures which have wiggle on their wings. The current understanding of these structures require at least three-component plasma model. In this work, ion-acoustic supersolitons are studied in three-component unmagnetized plasmas comprising of Boltzmann electrons, nonthermal (Cairn’s distribution) electrons and fluid cold ions. The supersoliton solutions are obtained for Mach number values beyond the existence of double layers. The effect of nonthermality, cold electron density and cold to hot electron temperature ratio is examined on ion-acoustic supersolitons. It is found that presence of nonthermal electrons significantly affect the existence of the supersolitons. The amplitude of the supersolitons decreases with the increase in the nonthermality for the fixed value of Mach number. Our results show that electric field and electrostatic potential of the supersolitons are more distorted which are obtained for Mach numbers closer to the double layer solutions than the far away solutions. Due to the lack of observations of these structures, either in space or laboratory plasmas, our theoretical model predictions can not to be compared directly. However, it is worth investigating the data on the electrostatic solitary structures observed by several satellites in the various region of the Earth’s magnetosphere.
Keywords: Supersolitons; Double layers; Ion acoustic waves